Inuit women and child inside snow house, Cape Fullerton, Hudson Bay, Canada - Comer, George (Creator); Lockwood, F.C. (Creator) (Ownership Statement: Mystic Seaport, 1901)
Three Inuit women and a child are seated inside a snow house, Cape Fullerton in Hudson Bay, Canada, January 6, 1901. Lifestyle Infrastructure Title supplied by cataloger. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Slide prepared by F.C. Lockwood of Brooklyn, New York, from an original photograph by Captain George Comer. Slide was used by Comer to illustrate lectures about his Arctic and seafaring experiences.